Traditional Composting, BoKashi and Takakura: Efficiency in the Degradation of Organic Waste - Danny A. Lizarzaburu Aguinaga; Elvia N. Saavedra Pinedo; Keera V. Bravo Guevara; Elmer Benites-Alfaro; Rosalina Orrego Cumpa (Chemical Engineering Transactions, 2023)
Currently, around the world, cities, and populations tend to dispose of all organic waste without any reuse option. Kaza et al., (2020) point out that only 4% of waste is recycled in underdeveloped countries. The impacts generated by these organic residues are gases such as SO2, NOx, CO, CO2, HC, benzene, chloroform, and methane, they produce too suspended particles in air and liquids with a high concentration of infectious biological and toxic elements called leachates; all can affect the health (respiratory and intestinal infections, conjunctivitis, etc.). In the city of Chachapoyas (Peru), 69 % of the waste are organic so is encouraged at the population the practice of compost production, it is due to potential of this in agricultural activities, avoiding too, the disposal of large volumes in landfills and the reduction of greenhouse gas emissions. The purpose of this research was determinate and compare the efficiency of the methods of composting: traditional, Bokashi and Takakura, to evaluate how is degrade the organic matter generated by this city in each case. For it, the three types of compost were characterized evaluate parameters such as final temperature (°C), humidity (%), pH, electrical conductivity (dS/m), Nitrogen (% dry material), Potassium (mg/L) and Phosphorus (mg/L), and the microorganisms present in each compost. The results showed a higher benefit for the Takakura composting method with 78.33 % in degradation, followed by 61.81 % in the Bokashi method and 45 % in traditional composting. Also, regarding the physicochemical characteristics showing that the Takakura method obtained the best values. Likewise, the number of bacteria and fungi showed ranges of good microbial activity in the compost for all forms.